(untitled) (Sindoro: Cendikia Pendidikan, 2025)
This study focuses on social support strategies to aid the emotional recovery of children with past traumas at the Liora Kasih Orphanage in Medan, North Sumatra. Children in orphanages often suffer from various emotional problems due to traumatic experiences such as abuse, neglect, or the loss of parents. The findings indicate that social workers play a vital role in supporting children’s psychosocial recovery through interventions such as play therapy, peer support groups, and strength-based approaches. These interventions contribute positively to the emotional well-being of the children.